Spin Glass State and Griffiths Phase in van der Waals Ferromagnetic Material Fe5GeTe2 - Jiaqi He; Yuan Cao; Yu Zou; Mengyuan Liu; Jia Wang; Wenliang Zhu; Minghu Pan (Nanomaterials)
The discovery of two-dimensional (2D) van der Waals ferromagnetic materials opens up new avenues for making devices with high information storage density, ultra-fast response, high integration, and low power consumption. Fe5GeTe2 has attracted much attention because of its ferromagnetic transition temperature near room temperature. However, the investigation of its phase transition is rare until now. Here, we have successfully synthesized a single crystal of the layered ferromagnet Fe5GeTe2 by chemical vapor phase transport, soon after characterized by X-ray diffraction (XRD), DC magnetization M(T), and isotherm magnetization M(H) measurements. A paramagnetic to ferromagnetic transition is observed at ≈302 K (TC) in the temperature dependence of the DC magnetic susceptibility of Fe5GeTe2. We found an unconventional potential spin glass state in the low-temperature regime that differs from the conventional spin glass states and Griffiths phase (GP) in the high-temperature regime. The physical mechanisms behind the potential spin glass state of Fe5GeTe2 at low temperatures and the Griffith phase at high temperatures need to be further investigated.